2016
DOI: 10.1590/0103-8478cr20141582
|View full text |Cite
|
Sign up to set email alerts
|

Acid and low temperature treatments on Salmonella Enteritidis inoculated in pork and its subsequent survival in simulated gastric fluid

Abstract: Acid and low temperature treatments on Salmonella Enteritidis inoculated in pork and its subsequent survival in simulated... Ciência

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“… Kim et al (2011) likewise reported the growth of S. Typhimurium at 5°C in kimbap, a Korean ready-to-eat food, while Kinsella et al (2007) observed the survival and increased growth of a S. Typhimurium strain on beef after 72 h at 4°C. A possible explanation for the various growth patterns of Salmonella at low temperatures could be the different strains studied, the different types of raw material, and the variations on the levels and types of competing indigenous microbiota that could affect the survival or growth of Salmonella ( Oscar, 2007 ; Silva et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“… Kim et al (2011) likewise reported the growth of S. Typhimurium at 5°C in kimbap, a Korean ready-to-eat food, while Kinsella et al (2007) observed the survival and increased growth of a S. Typhimurium strain on beef after 72 h at 4°C. A possible explanation for the various growth patterns of Salmonella at low temperatures could be the different strains studied, the different types of raw material, and the variations on the levels and types of competing indigenous microbiota that could affect the survival or growth of Salmonella ( Oscar, 2007 ; Silva et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…This recovery may have been caused by the variation in pH conditions of the small intestine, which permitted the recovery of viable bacterial cells inhibited by the acidity of the proventriculus. The recovery capacity of bacterial cells in the small intestine, after passing through the high acidity of the proventriculus, is related to the stress response that these microorganisms possess (Silva, Santos, Paes, & Vanetti, ). This multiple‐stress tolerance is attributed to several physiological changes that occur in the bacteria, such as changes in the composition of the cell wall, morphological changes and the development of the acid tolerance response to the acid environment (Merrell & Camilli, ), increasing the chances of survival of these microorganisms in the environment of the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%
“…The results from these studies had great benefit for understanding ingredients and their structures. However, there is no help to explain how degradation in human stomach environment during digestion, because the physiological pH of human fluid gastric can range from 1.50 to 3.50 and it works at around 37 °C (Corcoran et al, 2007;Marieb & Hoehn, 2010;Silva et al, 2016). According to the United States Pharmacopoeia (The United States Pharmacopeia, 1995), standard simulated gastric fluid is consists of 3.2 mg/mL pepsin in 0.03 M NaCl at pH 1.20 (hydrochloric acid is used).…”
Section: Introductionmentioning
confidence: 99%